The influence of role models in career decision making in two communities - Agana, Gregorio A. (Gregorio Accad) 1952-
It is the aim of this study to bring to light the possible influences affecting career decision-making among the Itawes of Enrile and Ibanags of Tuguegarao. It attempts to uncover what might well be a significant dimension to career development and career decision-making, the concept of role modeling. Towards this end, the research looked into the career choices of both groups, their reasons for their career choices and the aspects of role modeling as effects of certain socio-psychological factors present within the family unit and the community as a whole.